1985
DOI: 10.2134/agronj1985.00021962007700030004x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of N Fertilization on Earthworm and Microarthropod Populations in Kentucky Bluegrass Turf1

Abstract: Earthworms and microarthropods are abundant in turfgrass and may be important to thatch decomposition and nutrient recycling. There is little published information concerning the effects of cultural practices on the soil fauna in turf. The purpose of this study was to determine the influence of prolonged N fertilization on populations of earthworms, Collembola, and Acari involved h decomposition processes in Kentucky bluegrass, and to relate these effects to changes in soil pH and thatch accumulation. Six rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
1
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 8 publications
(11 reference statements)
2
19
1
1
Order By: Relevance
“…This is in line with microscopic observations showing more thatch degradation in samples from old velvet bentgrass sod receiving regular soil topdressing compared with sod that had not received topdressing for nearly 20 yr (Ledeboer and Skogley 1967). At the same time, there are numerous reports showing increasing N rates to exacerbate thatch problems in various turfgrass species (e.g., Meinhold et al, 1973;Potter et al, 1985;Davis and Dernoeden, 2002). At the same time, there are numerous reports showing increasing N rates to exacerbate thatch problems in various turfgrass species (e.g., Meinhold et al, 1973;Potter et al, 1985;Davis and Dernoeden, 2002).…”
Section: Thatchsupporting
confidence: 80%
See 1 more Smart Citation
“…This is in line with microscopic observations showing more thatch degradation in samples from old velvet bentgrass sod receiving regular soil topdressing compared with sod that had not received topdressing for nearly 20 yr (Ledeboer and Skogley 1967). At the same time, there are numerous reports showing increasing N rates to exacerbate thatch problems in various turfgrass species (e.g., Meinhold et al, 1973;Potter et al, 1985;Davis and Dernoeden, 2002). At the same time, there are numerous reports showing increasing N rates to exacerbate thatch problems in various turfgrass species (e.g., Meinhold et al, 1973;Potter et al, 1985;Davis and Dernoeden, 2002).…”
Section: Thatchsupporting
confidence: 80%
“…Skogley (1975) also found that an increase in annual fertilizer rate from 146 to 342 kg N haˉ1 did not infl uence organic matter content in mat samples from an 8-yr-old velvet bentgrass putting green. At the same time, there are numerous reports showing increasing N rates to exacerbate thatch problems in various turfgrass species (e.g., Meinhold et al, 1973;Potter et al, 1985;Davis and Dernoeden, 2002). Our data suggest that one reason for these contradictory results might be that topdressing rates were suffi cient to provide optimal conditions for thatch degradation in the studies by Skogley (Ledeboer and Skogley, 1967;Skogley, 1975) but not in other studies.…”
Section: Thatchcontrasting
confidence: 64%
“…Ammoniacal N sources can decrease pH near plant roots while nitrate can increase pH, subsequently aff ecting P availability depending on soil type (Gahoonia et al, 1992). Potter et al (1985) found routine applications of ammonium nitrate fertilizer over 7 yr signifi cantly reduced the pH of a silt loam. However, N source had no signifi cant eff ects on pH of either sand or silt loam root zones in our study and only occasionally aff ected turf characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…and reduced casting by more than 80% for at least 5 weeks in trials on a soil-based putting green (Potter et al, 2010) and also temporarily reduced populations of L. terrestris in lawn turf (Seamans et al, 2015). Some lumbricid earthworm species are intolerant of soil acidity, so application of sulfur or other soil-acidifying substances may reduce their casting (Potter et al, 1985(Potter et al, , 2013Baker et al, 2000), but we found no published data on the response of A. hupeiensis to soil acidification or on the efficacy of the organic sulfur product for earthworm cast suppression.…”
Section: Trialmentioning
confidence: 99%